Permodelan Resiko Sistem Manajemen Integritas Pada Jaringan Pipa Transmisi Gas Alam Di Energi Mega Persada (EMP) Bentu Ltd Dengan Menggunakan Standar API RP 581 - Ardi, Muhammad; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In order to identify the reliability level of the pipeline which is one of the company's assets stated by this critical equipment. Diversity in the gas production plant, an integrated methodology with economic operational conditions, equipment life and in accordance with the direction of achieving a reliable, safe goal for the entire life of the design. The solution to reduce the risk of decreasing production in the Oil and Gas industry sector is one of the risks caused by the low reliability of the pipeline, not even identified at all, the Pipeline Integrity Management System includes modeling or simulation carried out through a continuous assessment process of a system in terms of design, construction, operation, maintenance in accordance with natural gas pipelines. The action taken to implement this modeling is to find and integrate existing information, identify the causes of failure and carry out risk analysis, develop integrity management plans, implement integrity management programs namely inspection and surveiy, analyze the results to decide the right program (repair or replacement) of the pipeline network, evaluates the actions taken, then reports and makes continuous improvements.Keywords: Pipeline, inspection, maintenance, repair, Pipeline Integrity Management System, Risk assessment.